PENGARUH LINGKUNGAN KELAS TERHADAP SIKAP SISWA UNTUK PELAJARAN MATEMATIKA - Limpo, Joice Novita; Oetomo, Hasan; Suprapto, Maria Helena (HUMANITAS (Jurnal Psikologi Indonesia), 2013)
AbstrakAttitude plays a great role in studentâs learning behavior. This studyÂ was designed to investigate the contributions of classroom environment toÂ studentsâ attitude toward math. Participants in this study were 70 studentsÂ of Etika Dharma Catholic Junior High School in Surabaya. ClassroomÂ environment was measured using adaptation of what is happening inÂ This Class? (WIHIC) scale and attitude toward math was measured usingÂ a scale developed by the researcher. The result shows that there is aÂ significant positive correlation between classroom environment and attitudeÂ toward math (r = 0,359, p < 0,01), which means the more positive studentsâÂ perception of their classroom environment, the more positive their attitudeÂ towards math would be. The linear regression analysis shows that classroomenvironment effectively contributes 12,9% to studentsâ attitude toward mathÂ (r2 = 0,129). Classroom environment can be used to predict studentsâÂ attitude toward math, with the equation Y = 48,916 + 0,229 X Â± 23,023.Â Result shows that classroom environment has a significant influence onattitude toward math, although not too significant. This is due to the existenceÂ of other variables that may influence attitude toward math, such asÂ achievement, peers, teacher, and other environmental factors.Keywords: attitude toward math, classroom environment,math